2020
DOI: 10.1177/2633105520936623
|View full text |Cite
|
Sign up to set email alerts
|

Lacking Effects of Envelope Transcranial Alternating Current Stimulation Indicate the Need to Revise Envelope Transcranial Alternating Current Stimulation Methods

Abstract: In recent years, several studies have reported beneficial effects of transcranial alternating current stimulation (tACS) in experiments regarding sound and speech perception. A new development in this field is envelope-tACS: The goal of this method is to improve cortical entrainment to the speech signal by stimulating with a waveform based on the speech envelope. One challenge of this stimulation method is timing; the electrical stimulation needs to be phase-aligned with the naturally occurring cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 182 publications
0
15
0
Order By: Relevance
“…These studies found that the tACS did modulate speech comprehension, but that the best and worst phase shifts were highly variable between subjects (Riecke et al, 2018;Zoefel, Archer-Boyd and Davis, 2018). Similarly, related work on temporal delays between the sound and the neurostimulation waveform found large variability between subjects, and in one case no significant effect on the population level (Riecke et al, 2018;Wilsch et al, 2018;Erkens et al, 2020;Wang et al, 2020). In our previous work on the role of phase shifts in tACS with the speech envelope we employed, as in this study, natural speech in which syllables did not occur at a single fixed frequency and found a phase dependency of the resulting speech comprehension that was largely consistent across the different subjects.…”
mentioning
confidence: 90%
“…These studies found that the tACS did modulate speech comprehension, but that the best and worst phase shifts were highly variable between subjects (Riecke et al, 2018;Zoefel, Archer-Boyd and Davis, 2018). Similarly, related work on temporal delays between the sound and the neurostimulation waveform found large variability between subjects, and in one case no significant effect on the population level (Riecke et al, 2018;Wilsch et al, 2018;Erkens et al, 2020;Wang et al, 2020). In our previous work on the role of phase shifts in tACS with the speech envelope we employed, as in this study, natural speech in which syllables did not occur at a single fixed frequency and found a phase dependency of the resulting speech comprehension that was largely consistent across the different subjects.…”
mentioning
confidence: 90%
“…The copyright holder for this preprint this version posted April 12, 2021. ; https://doi.org/10.1101/2021.04.12.439458 doi: bioRxiv preprint worst phase shifts were highly variable between subjects (Riecke et al, 2018;Zoefel, Archer-Boyd and Davis, 2018). Similarly, related work on temporal delays between the sound and the neurostimulation waveform found large variability between subjects, and in one case no significant effect on the population level (Riecke et al, 2018;Wilsch et al, 2018;Erkens et al, 2020;Wang et al, 2020). In our previous work on the role of phase shifts in tACS with the speech envelope we employed, as in this study, natural speech in which syllables did not occur at a single fixed frequency and found a phase dependency of the resulting speech comprehension that was largely consistent across the different subjects.…”
Section: Multiple Linear Regressionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 29, 2021. ; https://doi.org/10.1101/2021.03.26.437107 doi: bioRxiv preprint 14 are still controversial. [52][53][54] Amplitude-modulated tACS (AM-tACS) was proposed as a promising way to allow for effective magnetoencephalography (MEG) or electroencephalography (EEG) signal reconstruction during electrical stimulation. However, similar to TI stimulation, studies on AM-tACS have also mostly focused on simulations, and no systematic experimental test to validate the effectiveness of AM-tACS in humans has been performed.…”
Section: Ti Stimulation Is Effective In the Human Motor Cortexmentioning
confidence: 99%